(Re-)shaping learning experiences in supply chain management and logistics education under disruptive uncertain situations - Salinas-Navarro, David Ernesto; Pacheco-Velazquez, Ernesto; da Silva-Ovando, Agatha Clarice (Frontiers in Education, 2024)
Introduction Disruptive uncertain events often necessitate universities to abruptly shift from face-to-face to remote online learning, posing challenges to instructional quality and learning outcomes. Remote online instruction may lack social interaction, educational resources, and practical activities, hindering effective learning. Methods This study presents an experiential learning framework designed to foster active learning experiences amidst disruptive uncertain events. The framework incorporates such events as study situations to enhance student motivation and engagement. A methodology for designing learning experiences is proposed, with a focus on incorporating real-world disruptions into educational settings. Results A case study is presented, detailing the implementation of the framework in supply chain management and logistics education at a private university in Bolivia, amidst the COVID-19 pandemic. Results indicate that the novel learning experience positively impacted student motivation and engagement, facilitating the achievement of learning outcomes. Discussion The initial implementation suggests that the novel learning experience positively impacted student motivation and engagement while achieving their intended learning outcomes. However, further instances of utilizing the proposed framework are necessary to ascertain its generalizability and effectiveness across diverse contexts and situations. Identifying similarities or invariances will help validate the applicability of this approach in different educational settings affected by disruptive uncertain events.